Research on the position-pressure master-slave control for a rolling shear hydraulic servo system - Jun, Wang (Strojniški vestnik, 2015)
The position-pressure master-slave control of hydraulic servo system is a dual closed-loop system, which takes position closed loop as the main control system, pressure closed loop as the supplementary, bringing these two seemingly contradictory theories together while simultaneously control the system. When the position error value is bigger than the threshold value, the system will transfer the pressure signal to the signal which will be added to the position signal, and regulate the system. This paper first builds a mathematical model of the hydraulic servo system position-pressure master-slave control, then simulates the system with AMEsim and Matlab softwares, which verifies the feasibility of this function. Finally, experiments are conducted using the new function, and the results show that position-pressure master-slave control can improve the precision and stability of hydraulic servo system; this new function can also be applied to other high speed, high precision and heavy equipment.
Keywords: hidravlični sistem; krmiljenje položaja; krmilni sistemi; natančnost; potujoče škarje; pretvorba; stabilnost